COVID-19 and social distancing among children and adolescents in Brazil - Barros, Fernando C; Hartwig, Fernando P; Barros, Aluísio J D; Menezes, Ana M B; Horta, Bernardo L; Struchiner, Cláudio J; Vidaletti, Luis Paulo; Silveira, Mariangela F; Mesenburg, Marilia A; Delagostin, Odir A; Hallal, Pedro C; Victora, Cesar G (Revista de Saúde Pública, 2021)
OBJECTIVE To estimate the prevalence of SARS-CoV-2 antibodies and the adherence to measures of social distancing in children and adolescents studied in three national surveys conducted in Brazil between May–June 2020. METHODS Three national serological surveys were conducted in 133 sentinel cities located in all 27 Federative Units. Multistage probability sampling was used to select 250 individuals per city. The total sample size in age ranges 0–9 and 10–19 years old are of 4,263 and 8,024 individuals, respectively. Information on children or adolescents was gathered with a data collection app, and a rapid point-of-case test for SARS-CoV-2 was conducted on a finger prick blood sample. RESULTS The adjusted prevalence of antibodies was 2.9% (2.2–3.6) among children 0–9 years, 2.2% (1.8–2.6) among adolescents 10-19 years, and 3.0% (2.7–3.3) among adults 20+years. Prevalence of antibodies was higher among poor children and adolescents compared to those of rich families. Adherence to social distancing measures was seen in 72.4% (71.9–73.8) of families with children, 60.8% (59.6–61.9) for adolescents, and 57.4% (56.9–57.8) for adults. For not leaving the house except for essential matters the proportions were 81.7% (80.5–82.9), 70.6% (69.6–61.9), and 65.1% (64.7–65.5), respectively. Among children and adolescents, social distancing was strongly associated with socioeconomic status, being much higher in the better-off families. CONCLUSIONS The prevalence of antibodies against SARS-CoV-2 showed comparable levels among children, adolescents, and adults. Adherence to social distancing measures was more prevalent in children, followed by adolescents. There were important socioeconomic differences in the adherence to social distancing among children and adolescents.